Concepts of the "roots" of Ukrainian statehood during the Ukrainian revolution - Тимків, Антон (ВПЦ "Київський університет", 2025)
Background. This article explores the concepts employed by political actors and governments during the era of the Ukrainian Revolution as a means of legitimizing the existence of Ukrainian statehood. The author analyzes how all state formations utilized historical narratives, symbols, and terminology to affirm their legitimacy. Particular attention is paid to the concepts of "Rus'" and the "Cossack myth," which played a crucial role in shaping national identity. Methods. The methodological framework of the article is based on the principle of historicism, as well as historical-comparative, historical typological, and historical-systemic methods. An interdisciplinary approach is applied, including stylistic and iconological analysis, particularly in the study of visual sources and symbolic representations. Results. The study examines how all state formations during the Ukrainian Revolution employed historical narratives, symbols, and terminology. Special attention is given to the concepts of "Rus'" and the "Cossack myth" as central elements in the construction of national identity. The article also analyzes the role and interpretation of symbols – especially the tryzub (trident)–terminology, and their visual representation in the Hetmanate and the Ukrainian People's Republic. It covers projects of coats of arms, flags, seals, the use of historical figures such as hetmans, and the formation of a national pantheon. Conclusions. The study concludes that despite internal contradictions and conflicts, all state entities during the revolutionary period strove to legitimize Ukraine's existence by drawing on the legacy of various historical periods to pursue a common goal – the affirmation of Ukrainian statehood.

Вступ. Присвячено дослідженню концепцій, що були застосовані діячами й урядами доби Української революції як засіб обґрунтування права на існування Української державності. Проаналізовано, як усі державні утворення використовували історичні наративи, символи та термінологію для утвердження своєї легітимності. Особливу увагу приділено концепціям "Русі" та "козацького міфу", що відігравали ключову роль у формуванні національної ідентичності. Розглянуто роль символів, зокрема тризубу, термінології та їхньої інтерпретації. Також порушено питання візуальної репрезентації Гетьманату й УНР: проєкти гербів, прапорів, печатки, використання історичних постатей, гетьманів і формування національного пантеону.  Методи дослідження. Методологічною основою статті є принцип історизму, історико-порівняльний, історико-типологічний та історико-системний методи. Використано міждисциплінарний підхід, стилістичний та іконологічний аналіз для дослідження візуальних джерел і символіки. Результати. Проаналізовано використання історичних наративів, символів і термінології всіма державними утвореннями періоду Української Революції. Значну увагу приділено концепціям "Русі" та "козацького міфу". Розглянуто проєкти гербів, прапорів, печатки, з'ясовано роль історичних постатей гетьманів і створення національного пантеону. Висновки. З'ясовано, що попри суперечності та конфлікти, усі державні утворення прагнули легітимізації України, використовуючи надбання минулого різних періодів для досягнення спільної мети утвердження української державності.
Концепція "коренів" української державності в добу Української революції
Keywords: Ukrainian Central Rada; Ukrainian People's Republic; Ukrainian State; Skoropadskyi; Hrushevskyi; Cossack myth; Rus'; Hetmanate; " History of Ruthenians".; УЦР; УНР; Українська Держава; Скоропадський; Грушевський; козацький міф; Русь; Гетьманщина; «Історія Русів».